Quality concern, role conflict, and excessive workload influencing interpersonal workplace deviant behavior among hotel employees in Kelantan - Owi, Siew Yen (2019)
Nowadays, issues of workplace deviant behavior in the workplace has become more serious. Employees play an important role to secure and increase profit for the business. Specifically, in the hotel industry, the role of the hotel employee is important in enabling the business to develop and remain competitive. The purpose of this study is to investigate factors that influence interpersonal workplace deviant behavior among hotel employees in Kelantan. The objective of this research is to evaluate, investigate and identify the relationship between the factors (quality concern, role conflict, and excessive workload) and interpersonal workplace deviant behavior. A purposive sampling technique was used to select respondents from registered hotels in Kelantan, Malaysia. The study used a quantitative approach through structured questionnaires developed from previous research. A total of 230 survey questionnaires were distributed; only 213 questionnaires were usable for analysis. The study used SPSS 25.0 to analyze the data. Methodologies such as One-way ANOVA and Multiple Regression Analysis were used to analyze the data. In general, the findings revealed that interpersonal workplace deviant behavior has a significant positive relationship with quality concern and excessive workload. Meanwhile, role conflict showed a negative relationship with interpersonal workplace deviant behavior. This thesis concludes with discussion of the findings and limitations of the study and suggestion for future research.